PERMAINAN TRADISIONAL KUCING DAN TIKUS UNTUK PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TK PERINTIS 2 KECAMATAN SUNGAI RAYA - Isturianingsih, Isturianingsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to describe the potential of the traditional cat and mouse game for the social and emotional development of children aged 5-6 years at Perintis 2 Kindergarten, Sungai Raya District. The research method is a descriptive method in the form of qualitative research. The data sources in this research are the class teacher and head of Kindergarten Perintis 2, Sungai Raya District. This data collection technique is observation, interviews and documentation. The results of this research show that, the game of cat and mouse in developing the potential of children aged 5-6 years in Kindergarten Perintis 2, Sungai Raya District, in the social emotional aspect, there are self-awareness abilities, a sense of responsibility for oneself and others, and prosocial behavior is very Good. This can be seen from the knowledge that teachers have regarding the use of the traditional game of cat and mouse when learning, the way teachers behave towards children and the actions taken by teachers.